Designing Entrepreneurship Experiments: A Review, Typology, and Research Agenda - Hsu, Dan K.; Simmons, Sharon A.; Wieland, Alice M. (Organizational Research Methods, 2017)
This article discusses the current and potential application of experimental methods to the study of entrepreneurship phenomena. Drawing on a review of experimental studies in entrepreneurship research, we discuss the advantages and disadvantages of experimental research designs for entrepreneurship research as a primer for those interested but not overly familiar with these methods. To advance research agendas and theory in the field, we introduce a typology of experimental manipulations that highlight alternative design choices based on the nature of their participant impact and realism of context. Finally, we provide an overview of areas of opportunity within the entrepreneurship literature for application of methods best suited to provide greater insight into the causal mechanisms at play.
Keywords: dept.mgt; peer-reviewed

Teaching international business as an opportunity to develop cultural sensitivity - Frank, Ellen J. (Journal of Teaching in International Business, 2017)
Business program graduates are expected to perform with cultural sensitivity in international and intercultural professional environments. In order to support student development of the necessary mindset, a variety of assignments and activities have been integrated into the undergraduate International Business (IB) course. This article describes several types of exercises that can be used by anyone teaching this course or one where cultural sensitivity is an important component. No quantitative data are presented, nor are any claims made to the efficacy of these assignments. But student comments point to increased cultural sensitivity and a better understanding of the issues of globalization. © 2017 Taylor & Francis Group, LLC.
8 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/118-584-012-132-547, pop00249 tex.type: [object Object]
Keywords: Cross-cultural awareness; Cultural sensitivity; Globalization; International business (IB); dept.mgt

Strategic conflict: A systems based pedagogical simulation - Stepanovich, Paul; Mueller, James (International Journal of Social Science and Education, 2017)
The paper describes a pedagogical simulation that allows students to explore strategic goal conflict within the context of systems theory. Systems theory emphasizes, among other things, complexity, non-linear relationships, unintended consequences, time delays, and dynamics. Another important aspect of systems thinking is contextual thinking, where objects or relationships cannot be taken as standalone or absolute, but are critically dependent on system structure and the environment. And while strategic planning has long emphasized the importance of environment, it may be difficult for students to experience or appreciate its importance in the planning process. The simulation provides an experiential exercise for a strategy course. The paper provides a summary of systems thinking and strategic goal conflict, a description of the simulation, teaching notes, and experience with the exercise.
Keywords: dept.mgt; ⛔ No DOI found